THE ROLE OF FOREIGN LANGUAGE PROFESSIONALLY ORIENTED IN FORMATION OF SELF-LEARNING SKILLS IN OF STUDENTS OF THE PEDAGOGICAL UNIVERSITY - Dorokhina, I.V. (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the problem of defining the contribution of foreign language professionally oriented to forming self-directed learning skills of Pedagogical University students.